IMPROVING INVENTORY MANAGEMENT AT RESTAURANT XYZ: A COMPREHENSIVE ANALYSIS OF SUPPLY CHAIN EFFICIENCY USING ECONOMIC ORDER QUANTITY (EOQ) MODEL - Azharudin, Moh. Aldi; Basri, Mursyid Hasan (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research investigates the implementation of the Economic Order Quantity (EOQ) model to enhance inventory management practices at Restaurant XYZ. The primary objective of the study is to determine the efficacy of the EOQ model in optimizing the supply chain and reducing overall inventory costs within the dynamic environment of the restaurant industry. Given the challenges posed by the perishable nature of many food items and the fluctuating customer demand, the research adapts the traditional EOQ framework to suit both perishable and non-perishable items, aiming to achieve a balance between minimizing stockouts and reducing excess inventory. The study employs a quantitative approach, utilizing historical sales and inventory data from Restaurant XYZ to calculate the optimal order quantities and compare them with existing inventory practices. The findings demonstrate that the EOQ model, when adjusted for specific industry variables such as spoilage rates and demand variability, significantly improves inventory turnover and reduces wastage. The implications of these results suggest that the EOQ model, with specific modifications, can be a valuable tool for improving financial efficiency and operational effectiveness in restaurants. This study contributes to the field by providing a tailored EOQ application strategy that enhances inventory management in the restaurant industry.